PELATIHAN DESAIN GRAFIS MENGGUNAKAN CORELDRAW UNTUK MENINGKATKAN KREATIVITAS MENDESAIN PADA SISWI SMK IBRAHIMY 1 SUKOREJO - Safitri Nurul Qomariyah; Firda Wati Husaini Kulsum; Zaehol Fatah (Jurnal Padamu Negeri, 2025)
Grapich design training using CorelDRAW is conducted with the aim of enhancing the design cretivity of students at SMK Ibrahimy 1 Sukorejo. This activity is designed as a form of informal learning that emphasizes hands-on practice so that participants can understand the basic techniques to continue with the form of visual works such as logos, brochures, product packaging, and more through an interactive approach involving materials, demonstrations, and individual practice exposure. Evaluation result show a significant improvement in technical skills and originality in the designs produced by the participants. Additionally, this activity promotes students’ confidence in their work and strengthens their willingness to engage with the creative industry. This training has proven to be an effective way to develop soft skills and personal potential in graphic design